The Implementation of Holistic and Balanced Education at Thursina International Islamic Boarding School (IIBS) Malang - Khairil Anwar; Akhsanul In'am; Khozin; Faridi (Universitas Muhammadiyah Malang, 2025)
This research focuses on implementing holistic and balanced education in pesantren, or boarding schools, at Thursina International Islamic Boarding School (IIBS) Malang, Indonesia. This research employs a qualitative data collection approach, including in-depth interviews, observations of sources, and documentation. Triangulating sources and methods collect the data validity technique. The study’s results indicate that using a holistic and balanced education approach helps Thursina IIBS students reach their full potential in a connected and supportive way. The educational process relies on the cognitive aspect and includes the life experience of students as a whole, both in affective and psychomotor aspects, in a balanced manner. The conclusion of this study shows that implementing the holistic and balanced education concept at Thursina IIBS Malang can develop students’ basic competencies through various learning activities, both in and outside the classroom and through various student activities. This research implies that it is a study for developing students’ basic potential in realizing the profile of graduates with Islamic personalities, global insight, and leadership spirit.